Об одном способе обнаружения слабых потоков ионизирующих излучений - Забулонов, Ю.Л.; Буртняк, В.М. (Моделювання та інформаційні технології, 2010)
The method of detection the low fluxes of ionizing radiation is proposed. The
characteristics of the proposed method are considered. The algorithm for its
implementation is described.